An analysis of Challenges of Paris Agreement on Climate Change after United States' Withdrawal: Emerging Role of EU, China and India (Economic Journal of Nepal, 2017)
The United States played a key role in clinching the Paris Agreement and in expediting the satisfaction process to facilitate the execution of the agreement as early as possible. The current political dispensation is not inclined to meet its previous commitment to reduce its CO2 emissions by 26 to 28 percent in 2005. The decision to withdraw of the US government has impelled decision makers around the world to reiterate their commitment to implement the Paris agreement. The European Union (EU) will have to assume a pro-active role in the long process of implementing the promises made in Paris. In view of the unwillingness of the United States to abide by its commitment the EU needs to fortify its strategic partnerships with other major emitters such as China and India. The objective of this paper is also to discuss that how the key players will cope with the emerging situations.